Metabolic Engineering of Escherichia coli for para-Amino-Phenylethanol and para-Amino-Phenylacetic Acid Biosynthesis - Mohammadi Nargesi, Behrouz; Sprenger, Georg A.; Youn, Jung-Won (Frontiers in Bioengineering and Biotechnology, 2019)
Aromatic amines are an important class of chemicals which are used as building blocks for the synthesis of polymers and pharmaceuticals. In this study we establish a de novo pathway for the biosynthesis of the aromatic amines para-amino-phenylethanol (PAPE) and para-amino-phenylacetic acid (4-APA) in Escherichia coli. We combined a synthetic para-amino-l-phenylalanine pathway with the fungal Ehrlich pathway. Therefore, we overexpressed the heterologous genes encoding 4-amino-4-deoxychorismate synthase (pabAB from Corynebacterium glutamicum), 4-amino-4-deoxychorismate mutase and 4-amino-4-deoxyprephenate dehydrogenase (papB and papC from Streptomyces venezuelae) and ThDP-dependent keto-acid decarboxylase (aro10 from Saccharomyces cerevisiae) in E. coli. The resulting para-amino-phenylacetaldehyde either was reduced to PAPE or oxidized to 4-APA. The wild type strain E. coli LJ110 with a plasmid carrying these four genes produced (in shake flask cultures) 11 ± 1.5 mg l−1 of PAPE from glucose (4.5 g l−1). By the additional cloning and expression of feaB (phenylacetaldehyde dehydrogenase from E. coli) 36 ± 5 mg l−1 of 4-APA were obtained from 4.5 g l−1 glucose. Competing reactions, such as the genes for aminotransferases (aspC and tyrB) or for biosynthesis of L-phenylalanine and L-tyrosine (pheA, tyrA) and for the regulator TyrR were removed. Additionally, the E. coli genes aroFBL were cloned and expressed from a second plasmid. The best producer strains of E. coli showed improved formation of PAPE and 4-APA, respectively. Plasmid-borne expression of an aldehyde reductase (yahK from E. coli) gave best values for PAPE production, whereas feaB-overexpression led to best values for 4-APA. In fed-batch cultivation, the best producer strains achieved 2.5 ± 0.15 g l−1 of PAPE from glucose (11% C mol mol-1 glucose) and 3.4 ± 0.3 g l−1 of 4-APA (17% C mol mol−1 glucose), respectively which are the highest values for recombinant strains reported so far.